The Translation of Similes in Andrea Hirata’s The Rainbow Troops - Barathayomi, Wieka (Universitas PGRI Sumatera Barat, 2015)
The aim of this research is to find out the translation strategies used by the translator to translate similes in Andre Hirata’s novel L a s k a r P e l a n g i from Indonesian into English. This research is descriptive qualitative. The data were taken from Andrea Hirata’s novel L a s k a r P e l a n g i and its translation The Rainbow Troops. The result of this research shows that there are several strategies used by the translator to translate similes which include: using simile of similar form and meaning, using simile of dissimilar form but similar meaning, and translate directly without using a simile.